Navigating the Quantum Era: Exploring Lightweight Quantum-Resistant Cryptography - Wai Kaey, Tan (LPPM STIKI Malang, 2024)
In the realm of cybersecurity, the emergence of quantum computing poses a significant threat to traditional cryptographic methods. Quantum algorithms such as Shor's algorithm challenge the security of widely used cryptographic schemes like ECC. As quantum computers advance, there is an urgent need to develop quantum-resistant cryptographic techniques. This research project aims to address this need by focusing on the development of lightweight quantum-resistant cryptography. The project aims to develop a National Institute of Standards and Technology (NIST) Approved lightweight quantum-resistant cryptographic algorithm that aligns with the resource constraints inherent in diverse applications and devices. By navigating the quantum era, the project seeks to provide practical, efficient, and deployable cryptographic solutions aligned with the resource constraints of diverse applications and devices.